Budget gaming behavior: Evidence in Indonesian manufacturing companies - SeTin SeTin; Roy Sembel; Yvonne Augustine (University of Merdeka Malang, 2019)
Budget gaming behavior in the budgeting process has a serious impact on organizational performance. This behavior continues to exist as a consequence of the prevalence of traditional budgeting practices. This unsolved budget behavior needs serious handling. Understanding this behavior through gathering evidence is the first step in controlling the practice of budget gaming. This study aims to obtain evidence about budget gaming practice in Indonesia. Data collection through interviews, surveys, and analysis of annual reports. Interviews were conducted on four managers of go public manufacturing companies. Survey through questionnaires to 31 managers. The analysis of the 2013-2017 annual report on directors' reports and management discussion reports on three companies. This study concluded that budget gaming practice still occurs in manufacturing companies in Indonesia and is still an important problem that has not yet been solved. This study also found that budget gaming is related to the performance evaluation system. The study result provides important information for stakeholders and researchers in understanding budget gaming behavior and finding solutions to minimize budget gaming practice.JEL Classification: M2, M40, M41DOI: https://doi.org/10.26905/jkdp.v23i2.2945